Opiate maintenance patients’ attitudes and self-reported adherence to protective measures against SARS-CoV-2 infections - Specka, Michael; Kröckert, Tobias; Trilling, Mirko; Bonnet, Udo; Schifano, Fabrizio; Scherbaum, Norbert (Frontiers in Psychiatry, 2023)
Background During the COVID-19 pandemic we assessed to which extent patients in opioid maintenance treatment (OMT) adhere to official recommendations regarding preventive intervention strategies against COVID-19. Methods Patients enrolled in two OMT clinics in Germany were interviewed applying a standardized questionnaire, which covered socio-demographic information, recent psychotropic substance use, recent social activities, the history of SARS-CoV-2 infection, attitudes toward official protection recommendations, and levels of adherence to these suggestions. Current mental and medical diagnoses were retrieved from medical files. In subjects without known infection and without vaccination, blood samples were tested for the identification of anti-SARS-CoV-2-S-antibodies. Interviews were performed between the end of May and the end of September 2021. Results Patients’ (n = 155) average age was 47 years; 74% were males. In addition to the opiate dependence, in nearly 80% of cases another medical disorder was recorded. The range of medical factors that predispose for severe COVID-19 outcomes were present in 39% of patients; 18% of the sample refused to be vaccinated. Nearly all patients reported having carried out a range of activities outside their residence during the week prior to the interviews, including visits of treatment facilities (86.5%; 95% confidence interval [80.2%; 91.0%]) or meeting with friends (64.5% [65.7–71.6%]). Despite the fact that only about 47.1% [39.2%; 55%] felt well informed about measures against infection, adherence to COVID-19 countermeasures was generally high: 83.9% [77.3; 88.8%] claimed to have worn face masks always/nearly always; social distancing was performed always/nearly always by 58.7% [50.8%; 66.2%]; and hand hygiene was conducted by 64.5% [56.7%; 71.6%] of participants. None out of n = 25 tests from unvaccinated subjects was positive for anti-SARS-CoV-2-S-antibodies. Psychiatric comorbidity and educational degree were not statistically significantly associated with attitudes and compliance, except that patients with lower education felt relatively worse informed. Conclusion Self-reported adherence to recommended non-therapeutic intervention strategies and vaccination rates were similar to the German general population. Provision of more health-related information tailored to OMT patients appears necessary.